DOES HIGH-RISK PROSTATE CANCER HAVE WORSE SURVIVAL AFTER RADICAL PROSTATECTOMY? - Tosho Ganev (Peytchinski Publishing, 2024)
Purpose: We examine if the division of patients into low-, moderate- and high-risk groups also corresponds to different overall and cancer-specific survival after radical prostatectomy. Materials/Methods: The object of the study were 872 patients who underwent radical prostatectomy in the Clinic of Urology in "St. Anna - Varna" Hospital for the period from April 17, 1996, until November 25, 2022. Results: Overall and cancer-specific survival are lower in the high-risk group. When we divide the overall survival into two groups - up to and over 5 years after the operation, then low- and moderate-risk groups have better survival only after the fifth year of the operation. Conclusions: High-risk prostate cancer has very good overall survival within 5 years after radical prostatectomy, which means that an operation is a reasonable option for the treatment of this type of tumor.